First inventory of marine debris on Alegranza, an uninhabited island in the Northeast Atlantic - Herrera Ulibarri, Alicia; Rivera, J. Alexis; Moreno, Teresa; Martínez Sánchez, Ico; Gómez Cabrera, María Milagrosa (Marine Pollution Bulletin, 2022)
Alegranza is the most northerly island of the Canary Islands archipelago, the first obstacle crossed by the Canary Current. From July to October 2020, six expeditions were led to the island to make a first inventory of marine debris and its possible source and origin. In total, 3667 objects weighing 321 kg were removed, excluding wooden objects. Of these, 97.7% were plastics, the most abundant being drink bottles (25.4%). While knowing the origin, source and pathway of debris is difficult, legible labels provided valuable information. In Alegranza, 66.7% of the legible bottle labels indicated Asian countries of manufacture, which is evidence that the source is maritime traffic in the region. The lobster trap license labels from the east coast of the United States and Canada were dated from 1999 to 2018, supporting both the exogenous origin and long lifetime in the ocean of these debris. 1,49 5,8 Q1 Q1 SCIE 11,0